Parvalbumin-Deficiency Accelerates the Age-Dependent ROS Production in Pvalb Neurons in vivo: Link to Neurodevelopmental Disorders - Janickova, Lucia; Schwaller, Beat (Frontiers in Cellular Neuroscience, 2020)
In neurodevelopmental disorders (NDD) including autism spectrum disorder (ASD) and schizophrenia, impairment/malfunctioning of a subpopulation of interneurons expressing the calcium-binding protein parvalbumin (PV) –here termed Pvalb neurons– has gradually emerged as a possible cause. These neurons may represent a hub or point-of-convergence in the etiology of NDD. Increased oxidative stress associated with mitochondria impairment in Pvalb neurons is discussed as an essential step in schizophrenia etiology. Since PV downregulation is a common finding in ASD and schizophrenia individuals and PV-deficient (PV-/-) mice show a strong ASD-like behavior phenotype, we investigated the putative link between PV expression, alterations in mitochondria and oxidative stress. In a longitudinal study with 1, 3 and 6-months old PV-/- and wildtype mice, oxidative stress was investigated in 9 Pvalb neuron subpopulations in the hippocampus, striatum, somatosensory cortex, medial prefrontal cortex, thalamic reticular nucleus (TRN) and cerebellum. In Pvalb neuron somata in the striatum and TRN, we additionally determined mitochondria volume and distribution at these 3 time points. In all Pvalb neuron subpopulations, we observed an age-dependent increase in oxidative stress and the increase strongly correlated with PV expression levels, but not with mitochondria density in these Pvalb neurons. Moreover, oxidative stress was elevated in Pvalb neurons of PV-/- mice and the magnitude of the effect was again correlated with PV expression levels in the corresponding wildtype Pvalb neuron subpopulations. The PV-dependent effect was insignificant at 1 month and relative differences between WT and PV-/- Pvalb neurons were largest at 3 months. Besides the increase in mitochondria volume in PV’s absence in TRN and striatal PV-/- Pvalb neurons fully present already at 1 month, we observed a redistribution of mitochondria from the perinuclear region towards the plasma membrane at all time points. We suggest that in absence of PV, slow Ca2+ buffering normally exerted by PV is compensated by a (mal)adaptive, mostly sub-plasmalemmal increase in mitochondria resulting in increased oxidative stress observed in 3- and 6-months old mice. Since PV-/- mice display core ASD-like symptoms already at 1 month, oxidative stress in Pvalb neurons is not a likely cause for their ASD-related behavior observed at this age.